MODIFIED BORON-TITANIUM AUSTENITIC STAINLESS-STEEL ALLOYS FOR POWER REACTORS - Hafez, Shaimaa; M.M. Eissa; S.U. El-Kameesy; R.M. Elshazly; El Fawkhry, M.K.; Saeed, Aly (International Journal of Engineering Technologies and Management Research, 2018)
Boron, Titanium and boron – titaniumaustenitic stainless steel alloys were developed to be used as a nuclear reactor shielding material. Three grades of steel alloys with base composition of AISI316 but having either Ti or B or Ti and B (SS316Ti, SS316B and SS316TiB) were designed and produced using 30 kg pilot plant medium frequency induction furnace at the same conditions. Samples of the properly treated steels were subjected to microstructure observation, hardness, tensile and impact testing. The microstructure observation revealed an austenitic phase in all investigated steel alloys. Among the investigated steels, the lowest corrosion rate was found in the modified steel containing B. The macroscopic-cross sections for neutrons > 10 keV, slow, and total slow neutrons were carried out using 241Am-Be neutron source. The developed boron and boron-titanium stainless steel alloys were found to have higher cross sections for neutrons > 10 keV, slow, and total slow neutrons than SS316 while the modified Ti- stainless steel has lower values for slow neutrons and neutrons > 10 keV than the standard stainless steel SS316. Moreover, the associated neutron half value layer (HVL) was calculated for each sample. Additionally, gamma ray shielding properties were performed for several gamma ray energies that emitted from 232Th radioactive source.